ANALYSIS OF PIPE NETWORK OPTIMIZATION FOR RAW WATER IN JABUNG SUB-DISTRICT, MALANG DISTRICT - Subandriyo, Putut; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Jabung District is a sub-district located in the Malang Regency area of 135.89 km2 or around 4.56 percent of the total area of Malang Regency. This sub-district consists of 15 villages, including Argosari, Gadingkembar, Gunungjati, Jabung, Kemantren, Kemiri, Kenongo, Ngadirejo, Pandansari Lor, Sidomulyo, Sidorejo, Slamparejo, Sukolilo, Sukopuro, and Taji. With a population of 74,311 people in 2020, with a population density of 592 people/km2. In Jabung District, especially in 4 villages, including Pandansari Lor Village, Gading Kembar Village, Argosari Village, and Kemiri Village, there is currently a water shortage. Siuk Source Potential has water potential large enough to meet the standard needs in these 4 villages by gravity. From the results of instantaneous discharge measurements during the dry season in 2021, it can be seen that the discharge in Sumber Siuk is 65 l/sec, and the planned collection to fulfill these 4 villages is 20 l/sec. Construction of the broncaptering and raw water distribution network was built in 3 stages. Before the physical implementation of the installation of distribution pipes in stage 3, a trial run was carried out from stage 1 and stage 2.